IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR ISLAM TERPADU AN-NIDA’ KOTA LUBUKLINGGAU - Mahmudan Mahmudan (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
Character education is becoming increasingly urgent to implement in our educational institutions considering awide range of non-educational behavior has now been penetrated in our educational institutions. Such behavior, amongothers: the phenomenon of violence, sexual abuse, mania business through schools, corruption and arbitrariness thatoccur among school. After conducting a preliminary study in the Elementary School Isam al-Nida ‘Lubuklinggau, it canbe concluded while, that the Elementary School Islam An-Nida’ Lubuklinggau is an educational institution that began tonotice the importance of character education.This study used a qualitative descriptive approach. In collecting the data,the authors using observation, interviews, and documentation.This study produced three findings: first from the aspect ofplanning is done in several ways, including: a) Designing school conditions conducive, b) Designing curriculum of charactereducation explicitly, c) Creating a curriculum characters integrative, d) Management of classrooms, e) environmentalmanagement outside the classroom. Both at the level of implementation is done, among others: a) Cooperation betweenthe school community, b) Applying the model, c) Habituation pray, d) Guidance Qur’an intensive, e) Appreciating thecreativity of learners, f) Establish a harmonious relationship between teachers and learners. Third at the level evalusinyado several things, among others: a) Cooperation with parents of learners (co parenting), b) strict supervision of thecharacter, c) Home visit (Home Visits), d) Issue a communication book.